Boundary layer flow of nanofluid over a moving surface in a flowing fluid using revised model with stability analysis - Jahan, S. (Elsevier Ltd, 2017)
This article reveals the boundary layer flow analysis of nanofluid past a moving surface in a uniform free stream with the physically more realistic approach by imposing both temperature and concentration fraction on the surface in such a way that nanoparticle concentration adjusts and flux becomes zero on the surface. In other word, nanoparticle fraction adjusts accordingly on the boundaries. The system of nonlinear ODEs is solved numerically using bvp4c function and shooting technique. With the help of various initial guesses, dual solutions are found up to a certain limit when the free stream and the plate are in the opposite directions. Then examined the stability of the solutions obtained using the method of stability analysis. The impact of various flow parameters on the skin friction coefficient and the local Nusselt number, the velocity, temperature and concentration distributions are conferred in detail. The reduced Nusselt number is estimated with the help of linear and quadratic regressions. For the validity, the comparison is made. Results indicate that the first (upper branch) solution is stable and thus, physically realizable. There is no effect on the reduced Nusselt number for any value of the Brownian motion parameter due to zero nanoparticle flux on the surface. On the other hand, the heat transfer rate decreases for higher values of the Schmidt number and thermophoresis parameter. The flow pattern behaved same as the stagnation point flow for the first (upper branch) solution but separated into two regions for the second (lower branch) solution. © 2017 Elsevier Ltd